A rapid assessment of community-wide HIV/STI intervention in China. Issue 1 (28th January 2005) - Wang, D B; Zhang, X J; Zhang, H B; Zhang, C Y; Su, B
Abstract : Background/objectives: The key to HIV/STI control is community-wide intervention (CWI) which depends heavily on continuous monitoring and evaluation. Unfortunately, comprehensive CWI assessment methodology and reports are generally lacking. This study developed, applied, and evaluated a rapid tool for assessing CWI in China. Methods: A total of 120 county level respondents in charge of county-wide responses to HIV/STI thoughout China were selected randomly and surveyed using a structured inventory consisting of three tiers of indicators developed via consensus group techniques. The respondents were asked to rate each of the indicators against a five grade (1–5) scale. 30 pairs of the same staff from within Anhui Province were surveyed to gauge inter-rater reliability. Results: Response rate for the nationwide survey was 85% and for inter-rater reliability survey, 90%. Correlation coefficients between the inter-rater ratings ranged from 0.68 to 0.95. The overall average rating of CWI in China was 2.85. Average ratings for the six first tier indicators, organisation and policy development, goals and objectives setting, project and action planning, resource exploitation, project and task implementation, and CWI evaluation were 2.87, 2.83, 2.67, 2.77, 3.26, and 2.71 respectively. Ratings derived for the 24 second tier indicators ranged from 2.1 to 3.86; while for the 96 third tier indicators, 1.90 to 4.40 Conclusions: The instrument developed proved to be reliable, useful, and easily applicable in common communities. Application of it in China revealed that a large gap exists between desired and actual CWI, and areas meriting particular attention include policy and incentives development, intervention planning and evaluation, and fund raising and utilisation.